Human resources marketing in Tesco Stores ČR a.s. - Řídká, Klára; Stříteský, Marek; Šikýř, Martin, 1974-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2011)
The thesis describes main aspects of human resources marketing, its objectives, tasks, tools and significance for employers. It focuses on the latest trends and approaches which are currently applied in human resources marketing. In the practical part the author describes the operation of human resources marketing in a selected company -- Tesco Stores ČR a.s.. It presents results of the research that focused on opinions and attitudes of pharmacists and students of pharmacy on selecting their employer. The aim of the thesis is to evaluate human resources marketing in Tesco Stores ČR a.s. and on the basis of the research results, to suggest suitable strategies to help the company to recruit employees for their chemist's.
Vedoucí práce: Marek Stříteský
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2011
Rok obhajoby 2011
Keywords: podniková ekonomika a management [obor dipl. práce]; diplomové práce; master's theses